2010
DOI: 10.1042/bj20101286
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of human GLRX5: iron–sulfur cluster co-ordination, tetrameric assembly and monomer activity

Abstract: Human GLRX5 (glutaredoxin 5) is an evolutionarily conserved thiol-disulfide oxidoreductase that has a direct role in the maintenance of normal cytosolic and mitochondrial iron homoeostasis, and its expression affects haem biosynthesis and erythropoiesis. We have crystallized the human GLRX5 bound to two [2Fe-2S] clusters and four GSH molecules. The crystal structure revealed a tetrameric organization with the [2Fe-2S] clusters buried in the interior and shielded from the solvent by the conserved β1-α2 loop, Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 162 publications
(128 reference statements)
5
123
0
Order By: Relevance
“…In contrast, we found that in the AtGRXS16 dimer, 65% of the Cys residues in the NTD (SVPELCGSVK) and 66% of the Cys residues in the CTD (SAPQCGFSQR), as readouts as free thiols in these assays, did not form an intramolecular disulfide bond (Table S2), which is consistent with the fact that the Cys residue in the "CGFS" motif is essential for Fe-S cluster binding (Fig. S5C) (20,21,23). These results also suggest that AtGRXS16-NTD could bind to the Grx domain bridged by an intramolecular disulfide bond and inhibit the Grx activity in vivo.…”
Section: Atgrxs16 Forms An Intramolecular Disulfide Bond To Regulate Itssupporting
confidence: 79%
“…In contrast, we found that in the AtGRXS16 dimer, 65% of the Cys residues in the NTD (SVPELCGSVK) and 66% of the Cys residues in the CTD (SAPQCGFSQR), as readouts as free thiols in these assays, did not form an intramolecular disulfide bond (Table S2), which is consistent with the fact that the Cys residue in the "CGFS" motif is essential for Fe-S cluster binding (Fig. S5C) (20,21,23). These results also suggest that AtGRXS16-NTD could bind to the Grx domain bridged by an intramolecular disulfide bond and inhibit the Grx activity in vivo.…”
Section: Atgrxs16 Forms An Intramolecular Disulfide Bond To Regulate Itssupporting
confidence: 79%
“…GRX1 is mainly localized in the cytosol but can be found in the MIS; it can be translocated into the nucleus and exported from the cell 159. GRX2 is expressed in the mitochondria,165 GRX3 in the cytosolic and nuclear compartment, and monothiol GRX5 has a mitochondrial translocation signal and shares the active site motif of GRX3 166. Evidence has also shown that the GRX system can also catalyse reversible protein glutathionylation,167 which is an important redox regulatory mechanism, and control the redox state of thiol groups168 in situations where the redox environment is being compromised.…”
Section: Regulatory Reactive Oxygen and Nitrogen Species Enzymes Exprmentioning
confidence: 99%
“…The role of Grx5 as an Fe/S cluster transfer protein is supported by the crystal structure of the human homologue GLRX5 with a bridging [2Fe-2S] cluster (73). The definition for bacterial GrxD as a cluster "carrier protein" cannot be adopted for mitochondria to avoid confusion with "mitochondrial carrier proteins" involved in inner membrane transport of metabolites (74).…”
Section: Chaperone-facilitated [2fe-2s] Cluster Release From Isu1 Andmentioning
confidence: 99%